Exogenous insulin‐like growth factor 1 attenuates cisplatin‐induced muscle atrophy in mice. Issue 6 (16th July 2021) - Sakai, Hiroyasu; Asami, Maho; Naito, Hiroaki; Kitora, Satoko; Suzuki, Yuta; Miyauchi, Yu; Tachinooka, Rei; Yoshida, Satoshi; Kon, Risako; Ikarashi, Nobutomo; Chiba, Yoshihiko; Kamei, Junzo
Abstract: Background: A reduction in the skeletal muscle mass worsens the prognosis of patients with various cancers. Our previous studies indicated that cisplatin administration to mice caused muscle atrophy. This is a concern for human patients receiving cisplatin. The insulin‐like growth factor 1 (IGF‐1)/phosphoinositide 3‐kinase (PI3K)/Akt pathway stimulates the rate of protein synthesis in skeletal muscle. Thus, IGF‐I can be a central therapeutic target for preventing the loss of skeletal muscle mass in muscle atrophy, although it remains unclear whether pharmacological activation of the IGF‐1/PI3K/Akt pathway attenuates muscle atrophy induced by cisplatin. In this study, we examined whether exogenous recombinant human IGF‐1 attenuated cisplatin‐induced muscle atrophy. Methods: Male C57BL/6J mice (8–9 weeks old) were injected with cisplatin or saline for four consecutive days. On Day 5, quadriceps muscles were isolated. Mecasermin (recombinant human IGF‐1) or the vehicle control was subcutaneously administered 30 min prior to cisplatin administration. A dietary restriction group achieving weight loss equivalent to that caused by cisplatin administration was used as a second control. C2C12 myotubes were treated with cisplatin with/without recombinant mouse IGF‐1. The skeletal muscle protein synthesis/degradation pathway was analysed by histological and biochemical methods. Results: Cisplatin reduced protein level of IGF‐1 by about 85% compared with the vehicle group and also reduced IGF‐1/PI3K/Akt signalling in skeletal muscle. Under this condition, the protein levels of muscle ring finger protein 1 (MuRF1) and atrophy gene 1 (atrogin‐1) were increased in quadriceps muscles (MuRF1; 3.0 ± 0.1 folds, atrogin‐1; 3.0 ± 0.3 folds, P < 0.001, respectively). The administration of a combination of cisplatin and IGF‐1 significantly suppressed the cisplatin‐induced downregulation of IGF‐1/PI3K/Akt signalling and upregulation of MuRF1 and atrogin‐1 (up to 1.6 ± 0.3 and 1.5 ± 0.4 folds, P < 0.001, respectively), resulting in diminished muscular atrophy. IGF‐1 showed similar effects in cisplatin‐treated C2C12 myotubes, as well as the quadriceps muscle in mice. Conclusions: The downregulation of IGF‐1 expression in skeletal muscle might be one of the factors playing an important role in the development of cisplatin‐induced muscular atrophy. Compensating for this downregulation with exogenous IGF‐1 suggests that it could be a therapeutic target for limiting the loss of skeletal muscle mass in cisplatin‐induced muscle atrophy.